Mid-infrared variability of γ-ray emitting blazars - Ayesha Anjum; C. S. Stalin; Suvendu Rakshit; Shivappa B. Gudennavar; Alok Durgapal (United Kingdom, 2022)
Using data from the Wide-field Infrared Survey Explorer, we studied the mid-infrared (mid-IR) 3.4 μm (W1-band) and 4.6 μm (W2-band) flux variability of γ-ray emitting blazars. Our sample consists of 460 flat spectrum radio quasars (FSRQs) and 575 BL Lacertae (BL Lac) objects. On intraday time-scales, the median amplitude of variability (σm) for FSRQs is 0.04-0.02+0.03 and 0.05-0.02+0.03 mag in W1 and W2 bands. For BL Lacs, we found a median σm in W1(W2) bands of 0.04-0.02+0.01 (0.04-0.02+0.02 mag. On long time-scales, for FSRQs we found a median σm of 0.44-0.27+0.28 and 0.45-0.27+0.27 mag in W1 and W2 bands, while for BL Lacs, the median values are 0.21-0.12+0.18 and 0.22-0.11+0.18 mag in W1 and W2 bands. From statistical tests, we found FSRQs to show a larger σm than BL Lacs on both intraday and long time-scales. Among blazars, low synchrotron peaked sources showed larger σm compared to intermediate synchrotron peaked and high synchrotron peaked sources. The larger σm seen in FSRQs relative to BL Lacs on both intraday and long time-scales could be due to them having the most powerful relativistic jets and/or their mid-IR band coinciding with the peak of the electron energy distribution. BL Lacs have low power jets and the observational window to traces the emission from low-energy electrons, thereby leading to low σm. In both FSRQs and BL Lacs predominantly a bluer when brighter behaviour was observed. No correlation is found between σm and black hole mass.